Enhancing Risk Management Education: The Impact of Classroom Simulations and Case-Based Teaching on Student Engagement and Learning Outcomes - Sugeng Pradikto; Mochamad Taufiq (AL-ISHLAH: Jurnal Pendidikan, 2025)
Risk management education often struggles to bridge the gap between theory and practice, with traditional teaching methods falling short in fostering student engagement and practical understanding. This study evaluates the effectiveness of classroom simulations and case-based learning in enhancing student engagement and learning outcomes in risk management education. A mixed-methods approach was used, combining a quasi-experimental one-group pretest-posttest design with qualitative analysis. The sample included 138 purposively selected 4th and 6th-semester students from the Economics Study Program at PGRI Wiranegara University. Quantitative data were analyzed using paired t-tests, while qualitative feedback from surveys and interviews was examined through Likert scale scoring and thematic analysis. Findings revealed a 35% improvement in average test scores, with pass rates increasing from 48% to 86%. Skills in applying risk management frameworks improved by 38%, indicating stronger practical competency. Additionally, 78% of students reported increased engagement, motivation, and participation, while over 70% expressed satisfaction with the learning methods. The integration of simulations and case-based learning significantly enhanced both cognitive and affective student outcomes. These results support the principles of experiential learning theory, underscoring the importance of interactive, real-world applications in education. Experiential learning methods improve student readiness for complex business environments and should be incorporated into higher education curricula. Future research should examine long-term impacts on professional skills and explore advanced technologies like Virtual Reality (VR) and Artificial Intelligence (AI) to further enrich simulation-based learning.